AMALAN PERTUKARAN ASING KONVENSIONAL: ANALISA BERDASARKAN PERSPEKTIF SYARIAH: Foreign Exchange in Conventional Banking Industry: An Analysis from Shariah Perspective - A Shukor, Abdul Rahman; Borhan, Joni Tamkin (Jurnal Syariah, 2017)
Foreign exchange is the largest market in the world and operates 24 hours a day. Foreign exchange consists of FX Spot, FX Forward, and FX Swap. Shariah guidelines stipulate that any currency exchange must adhere to the rule of al-á¹£arf whereby the exchange of different currencies must exchanged immediately hand-to-hand. Generally, conventional foreign exchange practice contradicts the requirements of al-á¹£arf because it involves an element of riba. However there are different views from Islamic scholars on the permissibility of these transaction. Therefore, the aim of this study is to analyse these foreign exchange transactions from a Shariah perspective. The result of this study shows that FX Spot complies with Shariah guidelines when subject to the requirements of al-á¹£arf. Meanwhile FX Forward and FX Swap are outside the bounds of these guidelines.